Lutein, Zeaxanthin, and meso-Zeaxanthin in the Clinical Management of Eye Disease. (24th December 2015) - Scripsema, Nicole K.; Hu, Dan-Ning; Rosen, Richard B.
Abstract : Lutein, zeaxanthin, and meso -zeaxanthin are xanthophyll carotenoids found within the retina and throughout the visual system. The retina is one of the most metabolically active tissues in the body. The highest concentration of xanthophylls is found within the retina, and this selective presence has generated many theories regarding their role in supporting retinal function. Subsequently, the effect of xanthophylls in the prevention and treatment of various eye diseases has been examined through epidemiological studies, animal studies, and clinical trials. This paper attempts to review the epidemiological studies and clinical trials investigating the effects of xanthophylls on the incidence and progression of various eye diseases. Observational studies have reported that increased dietary intake and higher serum levels of lutein and zeaxanthin are associated with lower risk of age-related macular degeneration (AMD), especially late AMD. Randomized, placebo-controlled clinical trials have demonstrated that xanthophyll supplementation increases macular pigment levels, improves visual function, and decreases the risk of progression to late AMD, especially neovascular AMD. Current publications on the preventive and therapeutic effects of lutein and zeaxanthin on cataracts, diabetic retinopathy, and retinopathy of prematurity have reported encouraging results.